Subjective Craving for Pornography and Associative Learning Predict Tendencies Towards Cybersex Addiction in a Sample of Regular Cybersex Users. - Snagowski, Jan; Laier, Christian; Duka, Theodora; Brand, Matthias (Sexual Addiction & Compulsivity)
There is no consensus regarding the diagnostic criteria of cybersex addiction. Some approaches postulate similarities to substance dependencies, for which associative learning is a crucial mechanism. In this study, 86 heterosexual males completed a Standard Pavlovian to Instrumental Transfer Task modified with pornographic pictures to investigate associative learning in cybersex addiction. Additionally, subjective craving due to watching pornographic pictures and tendencies towards cybersex addiction were assessed. Results showed an effect of subjective craving on tendencies towards cybersex addiction, moderated by associative learning. Thus, these findings indicate that such interactions might be crucial for the development of cybersex addiction.